Peripherien, Konflikte, Transformationen – Perspektiven einer kritischen Energiegeographie - M. Naumann; S. Becker; A. Bruns (Geographica Helvetica)
This introduction presents the fields of peripheries, conflicts and transformations as core topics of critical energy geographies. These fields point to different ways how the provision of energy is interwoven with social inequalities and uneven spatial development. Tackling the relations between energy technology and social power, the contributions to this Theme Issue highlight how power and resistance unfold in different spatial contexts and are linked to various notions of justice.